The Application of Pantun as an Oral Tradition of Malay Culture Among the Youth of Lam Province, Riau Archipelago, Tanjungpinang City - Ramli Muasmara, Ramli; Putri , Elfa Dzafira; Sumayah, Sumayah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to determine the conditions, supporting factors, and inhibiting factors of the implementation of pantun in youth fostered by LAM in Riau Islands Province in Tanjungpinang City. The study used a qualitative method with the research subjects being youth fostered by LAM. Data were collected through observation, interviews, and documentation. Primary data were obtained from the youth division of LAM and secondary data from LAM administrators and the Tanjungpinang City Cultural Office. The results of the study showed that youth fostered by LAM had understood the system of making good and correct pantun. They were also able to interact using pantun, although it took time to put it together. The success of the development was supported by the active role of the government and LAM administrators in preserving pantun. However, there were obstacles in the form of financial limitations, low abilities, and lack of interest from youth in participating in development. Nevertheless, the implementation of pantun in youth fostered by LAM was considered successful, although it still needed improvement to overcome various shortcomings.